1997
DOI: 10.1073/pnas.94.26.14654
|View full text |Cite
|
Sign up to set email alerts
|

Role of the major histocompatibility complex class IIEagene in lupus susceptibility in mice

Abstract: The gene(s) encoded within major histocompatibility complex (MHC) act as one of the major genetic elements contributing to the susceptibility of murine systemic lupus erythematosus (SLE

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
19
0

Year Published

1998
1998
2019
2019

Publication Types

Select...
4
4

Relationship

3
5

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 34 publications
2
19
0
Order By: Relevance
“…Because the development of SLE is dependent on CD4 ϩ T cells (3) and is blocked by treatment with anti-I-A Abs (4), the MHC class II molecules are probably involved in the development of lupuslike autoimmune syndrome. A role for MHC molecules in the regulation of murine SLE has been further supported by several genetic studies in H2 congenic lupus-prone mice (5)(6)(7)(8)(9)(10). Although little is known about how certain MHC alleles regulate the development of SLE, we have previously shown that the MHC class II Ea gene encoding the I-E ␣-chain (E␣-chain) may act as a lupus protective gene in mice, because the introduction of two copies of the Ea d transgene (Ea-Tg) in the lupus-prone E␣-chain-deficient BXSB strain (I-E Ϫ , H2 b ) is sufficient to prevent the development of SLE (10).…”
Section: S Ystemic Lupus Erythematosus (Sle)mentioning
confidence: 88%
“…Because the development of SLE is dependent on CD4 ϩ T cells (3) and is blocked by treatment with anti-I-A Abs (4), the MHC class II molecules are probably involved in the development of lupuslike autoimmune syndrome. A role for MHC molecules in the regulation of murine SLE has been further supported by several genetic studies in H2 congenic lupus-prone mice (5)(6)(7)(8)(9)(10). Although little is known about how certain MHC alleles regulate the development of SLE, we have previously shown that the MHC class II Ea gene encoding the I-E ␣-chain (E␣-chain) may act as a lupus protective gene in mice, because the introduction of two copies of the Ea d transgene (Ea-Tg) in the lupus-prone E␣-chain-deficient BXSB strain (I-E Ϫ , H2 b ) is sufficient to prevent the development of SLE (10).…”
Section: S Ystemic Lupus Erythematosus (Sle)mentioning
confidence: 88%
“…Because the expression of two copies of the Ea gene is capable of providing protection from SLE (8,9,32), the possible role of the MHC class II Ea gene as a lupus-protective gene in mice is likely to be influenced by the host MHC haplotype. However, it should be stressed that the effect of the Ea d transgene can be modulated by genetic factors other than the MHC class II genes present in the genetic background of individual lupus-prone mice.…”
Section: Discussionmentioning
confidence: 99%
“…BXSB.H-2 d , BXSB.H-2 k , and NZB.H-2 b congenic mice, created by backcross procedures at the 12th, 12th, and 10th generations, respectively, were described (6,8,15). NZB and MRL mice were purchased from Bomholtgard (Ry, Denmark).…”
Section: Micementioning
confidence: 99%
See 1 more Smart Citation
“…An association between HLA class II alleles and specific autoantibody generation is consistent with the concept of an Ag-driven process involving Th cell recognition. In previous studies of MHC and murine lupus, autoantibody production and lupus susceptibility were linked to the class II I-E-deficient haplotype carried in H2 b mice in BXSB (41), (NZB ϫ BXSB)F 1 (42,43), (MRL ϫ BXSB)F 1 (44), and B6/lpr mice (37). I-E␣, which is a homolog of human DR␣-chain, is deficient in H2 b mice due to a deletion of the promoter region of the Ea gene (45).…”
Section: Discussionmentioning
confidence: 99%